Electrochemical Study of Interfacially Synthesized Polycarbazole with Different Oxidants - Kumar A.; Tiwari M.; Prakash R. (My University, 2025)
This work focused on the morphology-controlled electrochemical impedance spectroscopic (EIS) studies of polycarbazole (PCz) in two different electrolytes. PCz is synthesized through controlled interfacial polymerization by using two different oxidizing agents, (NH4)2S2O8 (APS) and KMnO4. Voltammetric and EIS studies were carried out to explore charge-transfer properties in the vicinity of modified PCz/glassy carbon (GC) and PCz/Pt electrodes with different electrolytes that have different-sized anions. It has been observed that PCz-APS exhibits enhanced electron-transfer kinetics compared to PCz-KMnO4 at either electrode (GC or Pt) in a supporting electrolyte with a smaller anion size. This is attributed to its favorable diffusion inside the porous polymer film, resulting in easy ion exchange at the electrode surface. The morphology-controlled synthesis approach presented herein is extremely significant for chemical sensors, biosensors, and catalytic applications, owing to its high electroactivity. © 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.